2006
DOI: 10.1182/blood-2006-03-007013
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry predicts nucleophosmin (NPM) mutations in acute myeloid leukemia

Abstract: IntroductionAcute myeloid leukemia (AML) is a clinically and molecularly heterogeneous disease. Cytogenetic and/or molecular studies are used to assign 30% to 40% of AML cases carrying specific genetic lesions (eg, t(15;17), t(8;21) or Inv(16)) to different prognostic subgroups in order to monitor minimal residual disease and to select patients who could benefit from targeted therapies. 1 However, they cannot be applied to 40% to 50% of patients with AML who at conventional cytogenetics exhibit a normal karyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
179
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(192 citation statements)
references
References 36 publications
10
179
3
Order By: Relevance
“…34,35 Although there were too few cases to attempt formal statistical comparisons regarding the NPM1 or FLT3 gene mutations, survival of the acute myeloid leukemia ex chronic myelomonocytic leukemia cases containing the NPM1 mutation were generally favorable compared with the other patients. This finding, as well as the rapid progression of NPM1-mutated chronic myelomonocytic leukemia patients to acute myeloid leukemia in our series and in another published series, 24 suggests that cases diagnosed as chronic myelomonocytic leukemia with an NPM1 mutation may actually represent early de novo acute myeloid leukemia exhibiting dysplastic features and monocytosis mimicking chronic myelomonocytic leukemia. 36 It may thus be useful to screen chronic myelomonocytic leukemia cases for NPM1 mutation and carefully follow cases with NPM1 mutation for possible rapid transformation to 'bona fide' acute myeloid leukemia.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…34,35 Although there were too few cases to attempt formal statistical comparisons regarding the NPM1 or FLT3 gene mutations, survival of the acute myeloid leukemia ex chronic myelomonocytic leukemia cases containing the NPM1 mutation were generally favorable compared with the other patients. This finding, as well as the rapid progression of NPM1-mutated chronic myelomonocytic leukemia patients to acute myeloid leukemia in our series and in another published series, 24 suggests that cases diagnosed as chronic myelomonocytic leukemia with an NPM1 mutation may actually represent early de novo acute myeloid leukemia exhibiting dysplastic features and monocytosis mimicking chronic myelomonocytic leukemia. 36 It may thus be useful to screen chronic myelomonocytic leukemia cases for NPM1 mutation and carefully follow cases with NPM1 mutation for possible rapid transformation to 'bona fide' acute myeloid leukemia.…”
Section: Discussionsupporting
confidence: 78%
“…17 NPM1 and FLT3 Mutation Analysis NPM1 and FLT3 mutation status was obtained from available molecular diagnostic reports of acute myeloid leukemia, myelodysplastic syndrome, and chronic myelomonocytic leukemia cases. For the chronic myelomonocytic leukemia and acute myeloid leukemia ex chronic myelomonocytic leukemia cases with available paraffin-embedded material, NPM1 immunohistochemical staining was performed on deparaffinized bone marrow trephine sections 24 using the FLEX monoclonal mouse anti-human nucleophosmin antibody, Clone 376 (ready-to-use; Dako North America, Carpinteria, CA, USA) incubated overnight at 4 1C after antigen retrieval. The secondary antibody Mouse HRP (incubated for 15 min at room temperature) and the DAB Chromogen from Dako kit (K4006) were used.…”
Section: Cytogeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we have found that in human bone marrow, early progenitors, such as proerythroblasts or promyelocytes, express much more nuclear nucleophosmin than terminally differentiated cells, such as normoblasts or neutrophils. The usual positivity of NPM1wt in paraffin-embedded samples is 'nucleus-restricted, diffuse' rather than nucleolar, 26,45 reflecting the limits of immunohistochemical staining of paraffin sections in detecting subnuclear structures, such as nucleoli or nuclear bodies. 46 In normal human tissues, immunohistochemistry also identifies a small percentage of cells that express nucleophosmin in cytoplasm in the absence of NPM1 mutations.…”
Section: Native Npm1 Is a Nucleolar Protein With Ubiquitous Tissue Exmentioning
confidence: 99%
“…29 This is the hallmark of this kind of leukemia that can be detected by immunohistochemistry. 30 Because of its distinctive features, AML with NPM1 mutations has been included as a provisional distinct entity in the 2008 WHO classification of myeloid neoplasms. 31 The observation that AML-associated NPM1 mutations lead to the replacement of one or both of Trp288 and Trp290, and consequently alter the hydrophobic core of the C-terminal domain, led investigators to try to correlate the folding mechanism of the protein (wild-type versus the mutated one) with the altered cellular localization.…”
Section: Aml-associated Npm1 Mutations: Implications For Protein Stabmentioning
confidence: 99%